2021
DOI: 10.5304/jafscd.2021.102.026
|View full text |Cite
|
Sign up to set email alerts
|

Community engagement and the promotion of sustainable diets: Lessons from a grassroots meat reduction campaign

Abstract: Decreasing the consumption of meat and dairy has been identified as an effective strategy for protecting the health of humans and the planet. More specifically, transitioning to diets that are lower in animal-source foods and higher in fruits, vegetables, legumes, and whole grains offers a promising opportunity to better align consumer behaviors with contemporary nutritional and ecological goals. However, given the limited understanding of how these changes in dietary behaviors can be best promoted, there is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 72 publications
2
11
0
Order By: Relevance
“…The results from our joint analysis were mostly consistent with earlier research supporting the value of integrated approaches to meat reduction (Kahn-Marshall and Gallant, 2012; Gittelsohn and Lee, 2013;Vo et al, 2019;Ramsing et al, 2021). In addition to replicating these general findings, we were also able to use our novel classification scheme to distinguish between three different types of meat reduction approaches, with multimodal interventions outperforming interventions targeting the choice architecture of the retail environment and conscious decision-making processes alone, independent of the number of strategies involved.…”
Section: Summary Of Main Findingssupporting
confidence: 90%
“…The results from our joint analysis were mostly consistent with earlier research supporting the value of integrated approaches to meat reduction (Kahn-Marshall and Gallant, 2012; Gittelsohn and Lee, 2013;Vo et al, 2019;Ramsing et al, 2021). In addition to replicating these general findings, we were also able to use our novel classification scheme to distinguish between three different types of meat reduction approaches, with multimodal interventions outperforming interventions targeting the choice architecture of the retail environment and conscious decision-making processes alone, independent of the number of strategies involved.…”
Section: Summary Of Main Findingssupporting
confidence: 90%
“…The results from our joint analysis were mostly consistent with earlier research supporting the value of integrated approaches to meat reduction (Kahn-Marshall and Gallant, 2012;Gittelsohn and Lee, 2013;Vo et al, 2019;Ramsing et al, 2021). In addition to replicating these general findings, we were also able to use our novel classification scheme to distinguish between three different types of meat reduction approaches, with multimodal interventions outperforming interventions targeting the choice architecture of the retail environment and conscious decision-making processes alone, independent of the number of strategies involved.…”
Section: Summary Of Main Findingssupporting
confidence: 85%
“…In France, a large cross-sectional survey showed that those who participated in “Green Monday” were more likely to be women, more educated, and with higher self-rated affluence compared with controls ( 162 ). A community survey of Meatless Monday participation in Bedford, New York showed that participants were more likely to be women and with higher income but no significant difference in education level compared with controls ( 163 ). Meatless Monday was evaluated for perceived message effectiveness in an online randomized study of 1,244 US adults aged 18 years and older ( 164 ).…”
Section: Impact Of the Meatless Monday Campaignmentioning
confidence: 99%